Obstacles to the Nebras Drug Prevention Program: A Study of the Educational Environment Program - Alshehri, Ayah Hezam (Journal of Humanities & Social Sciences, 2021)
To identify the nature of the programs offered through Nebras program for the educational environment, and the goals described for Nebras for the educational environment, to identify the external obstacles represented in the social and cultural obstacles and the internal obstacles related to the administrative and technical aspect related to beneficiaries and the environment in which the program is applied. Study population consisted of (15) in charge of the educational environment program in Nebras in Riyadh region. A sample of (370) female students selected from the offices of education: The Guard, Al Nahda education office and Al Rawabi education office. In addition to a sample of (12) female student guides who are in charge of the implementation of the educational environment program in these schools. The study utilized the descriptive analytical approach and used the questionnaire to collect data. The study found that the most prominent programs offered in the educational environment are the awareness programs for female students about how to use their leisure time to benefit them, the most important programs, from the viewpoint of the female students, were introductory bulletins programs of free call service at the National Center for Addiction Consultation, followed in importance by video presentation programs about the national project for drug prevention, the most important objectives described for Nebras for the educational environment were, to raise the level of awareness of female teachers and students about the danger of drugs and psychotropic substances then to enhance self- immunity of female students towards negative practices. The study recommended that the National Committee for Drug Control should pay attention to the necessity of bringing families and the community together in raising awareness of the importance of the educational environment program because they play a fundamental role in supporting the participation of female students in the program, and that the Ministry of Education should allocate specific times and quotas to participate in educational environment programs and empty female students and counselors to participate in these programs. The study also recommended that the school be concerned with activating the material and moral support for the female guides based on the program, and the participating students effectively and motivating them.
Keywords: drug prevention; Nebras program; secondary stage; obstacles